Association between thermal responses, medical events, performance, heat acclimation and health status in male and female elite athletes during the 2019 Doha World Athletics Championships. Issue 8 (14th February 2022) - Racinais, Sebastien; Havenith, George; Aylwin, Polly; Ihsan, Mohammed; Taylor, Lee; Adami, Paolo Emilio; Adamuz, Maria-Carmen; Alhammoud, Marine; Alonso, Juan Manuel; Bouscaren, Nicolas; Buitrago, Sebastian; Cardinale, Marco; et al.
Abstract : Purpose: To determine associations between thermal responses, medical events, performance, heat acclimation and health status during a World Athletics Championships in hot-humid conditions. Methods: From 305 marathon and race-walk starters, 83 completed a preparticipation questionnaire on health and acclimation. Core (Tcore ; ingestible pill) and skin (Tskin ; thermal camera) temperatures were measured in-competition in 56 and 107 athletes, respectively. 70 in-race medical events were analysed retrospectively. Performance (% personal best) and did not finish (DNF) were extracted from official results. Results: Peak Tcore during competition reached 39.6°C±0.6°C (maximum 41.1°C). Tskin decreased from 32.2°C±1.3°C to 31.0°C±1.4°C during the races (p<0.001). Tcore was not related to DNF (25% of starters) or medical events (p≥0.150), whereas Tskin, Tskin rate of decrease and Tcore -to-Tskin gradient were (p≤0.029). A third of the athletes reported symptoms in the 10 days preceding the event, mainly insomnia, diarrhoea and stomach pain, with diarrhoea (9% of athletes) increasing the risk of in-race medical events (71% vs 17%, p<0.001). Athletes (63%) who performed 5–30 days heat acclimation before the competition: ranked better (18±13 vs 28±13, p=0.009), displayed a lower peak Tcore (39.4°C±0.4°C vs 39.8°C±0.7°C, p=0.044) and larger in-race decrease in Tskin (−1.4°C±1.0°C vs −0.9°C±1.2°C, p=0.060), than non-acclimated athletes. Although not significant, they also showed lower DNF (19% vs 30%, p=0.273) and medical events (19% vs 32%, p=0.179). Conclusion: Tskin, Tskin rate of decrease and Tcore -to-Tskin gradient were important indicators of heat tolerance. While heat-acclimated athletes ranked better, recent diarrhoea represented a significant risk factor for DNF and in-race medical events.